Mass Spectrometry in the Clinical Laboratory: Beyond Toxicology to Endocrinology and Microbiology - Alzahrani, Ali Saeed Abdullah; Hani Awied Aied Alharbi; Ali Abdullah Mohammed Alsaab; Yasir Ali Muhammad Al-Zahrani; Emad Ali Muhsin Alattas; Ahmed Abdullah Orepi; Ali Abdullah Alzahrani; Majed Abdulrahman Alrashidi; Mansour Butayhan Al Mabdi; Ali Ahmed Alomari Alzhrani (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The clinical laboratory has witnessed a paradigm shift with the introduction of mass spectrometry (MS) into its activities, extending its role way beyond the traditional field of toxicology. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review comprehensively discusses the revolutionizing impact of tandem mass spectrometry (MS/MS) and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS on the diagnosis and management of human disease, particularly in endocrinology and microbiology. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Synthesis of concepts, applications, and relative advantages of these MS methods from the current literature between 2015 and 2024 was reviewed. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Liquid chromatography-tandem mass spectrometry (LC-MS/MS) emerged as the gold standard in endocrinology with improved specificity for steroid, thyroid hormone, and vitamin measurement, thereby enabling accurate diagnosis of complex disorders. Meanwhile, MALDI-TOF MS has revolutionized clinical microbiology by providing quick, accurate, and cost-effective microbial identification, with an appreciable shortening of the time to effective antimicrobial therapy. Further, MS/MS remains the basis of newborn screening for congenital errors of metabolism. Despite challenges like standardization and cost, newer directions like mass spectrometry imaging and ambient ionization techniques promise further advancements. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The findings verify that MS/MS and MALDI-TOF MS lead the path of the modern clinical laboratory’s commitment to deliver precise, individualized, and prompt patient treatment.